DINÂMICA IMOBILIÁRIA E ESTRUTURAÇÃO INTRA-URBANA: ESTUDO DE CASO DOS CONDOMÍNIOS HORIZONTAIS FECHADOS NO SETOR SUL DE UBERLÂNDIA (MG) - BOTELHO, Diego Nogueira (2008)
This work aim to comprehend the role played by the housing market in the urban dynamic structure of Uberlândia. For it we analyse the transformations provocade by the closed allotted land in the Uberlândia urban space, associated to the market within the period of 2000-2005. Due to the importance that the housing market sector have in the expansition process of the urban landscape, in the last decades the product that deserves an enhanced position are the closed allotted land, as they were the main responsible by deep transformations in the local housing market. This new product start to spread in the Uberlândia landscape form 2000 s, and according to the Council, there are currently 42 horizontal closed allotted land, located mainly in the city south, the so called nobel area ; that historically was created to house wealth class and for a long time were scarcely in habited although this type of investment, has already been in the urban landscape since the 80 s, occupying significatives parts of urban landscape, changing it s geometric for, reducing the number of foreseen lands for each specific area and substituting the front view for walls